HOMEWORK ONLINE" AS AN INNOVATIVE TECHNOLOGY FOR TEACHING A FOREIGN LANGUAGE - Ergasheva , Jasmina Shuxratovna.; Ziyadullayeva, Aziza Akmalovna (GOLDEN BRAIN, 2024)
The article raises the problem of reducing the completion of homework in a foreign language, as one of the main ways to consolidate the material obtained in a practical lesson, control and self-control. Using the Internet service Learningapps.org The author suggests an experiment on the topic of "Homework online" with a group of students; which contributed to the popularization of homework among students, increased the percentage of knowledge quality and developed the skill of working with information.